2015
DOI: 10.7150/thno.11692
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM Aptamer-mediated Survivin Silencing Sensitized Cancer Stem Cells to Doxorubicin in a Breast Cancer Model

Abstract: Understanding the molecular basis of drug resistance and utilising this information to overcome chemoresistance remains a key challenge in oncology. Here we report that survivin, a key protein implicated in drug resistance, is overexpressed in cancer stem cell pool of doxorubicin-resistant breast cancer cells. Moreover, by utilising an active targeting system consisting of an RNA aptamer targeted against the epithelial cell adhesion molecule and a Dicer substrate survivin siRNA, we could deliver a high dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 58 publications
2
59
0
Order By: Relevance
“…In this regard, several shortened aptamers have been proposed with different analytes (Gopinath et al 2006a), as smaller aptamers perform better as chimeras because longer aptamers may undergo degradation. In recent years, there has been an increasing interest in the applications of aptamer chimeras in the field of therapeutics Rohde et al 2015;Subramanian et al 2015;Wang et al 2015;Diao et al 2016). Rohde et al (2015) demonstrated a transferrin receptor and microRNA aptamer chimera (mir-126) that promoted sprouting of endothelial cells and suppressed recruitment of breast cancer cells.…”
Section: Aptamer-based Chimerasmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, several shortened aptamers have been proposed with different analytes (Gopinath et al 2006a), as smaller aptamers perform better as chimeras because longer aptamers may undergo degradation. In recent years, there has been an increasing interest in the applications of aptamer chimeras in the field of therapeutics Rohde et al 2015;Subramanian et al 2015;Wang et al 2015;Diao et al 2016). Rohde et al (2015) demonstrated a transferrin receptor and microRNA aptamer chimera (mir-126) that promoted sprouting of endothelial cells and suppressed recruitment of breast cancer cells.…”
Section: Aptamer-based Chimerasmentioning
confidence: 99%
“…Rohde et al (2015) demonstrated a transferrin receptor and microRNA aptamer chimera (mir-126) that promoted sprouting of endothelial cells and suppressed recruitment of breast cancer cells. An aptamersiRNA polymeric nanocomplex was designed for targeting epithelial cell adhesion molecules, which are overexpressed in solid tumors (Subramanian et al 2015), and Wang et al (2015) used the aptamer-siRNA chimera to silence survivin in cancer cells and enhance the effect of doxorubicin, even when used in small amounts. Very recently, using an antiprostate specific membrane antigen aptamer-siRNA chimera, Diao et al (2016) specifically controlled the growth of a prostate tumor.…”
Section: Aptamer-based Chimerasmentioning
confidence: 99%
“…In a very aggressive triple-negative breast cancer xenograft model, the EpCAM-AsiC treatment caused complete tumor regression [41]. Further, anti EpCAM aptamer-mediated survivin silencing has been explored to sensitize breast cancer stem cells to Doxorubicin [42]. …”
Section: Aptamer-drug and Oligonucleotide Systemsmentioning
confidence: 99%
“…The siRNA accumulated at the tumor site and resulted in an 80% knockdown of the survivin gene, which inhibits apoptosis and promotes chemoresistance in CSCs. When combined with doxorubicin, the aptamer-siRNA chimera improved survival rates of tumor-bearing mice, [37] demonstrating the effectiveness of anti-CSC RNAi in vivo …”
Section: Silencing Oncogenesmentioning
confidence: 99%